Interplay of land governance and large-scale agricultural investment: Evidence from Ghana and Kenya - Kerstin Nolte; Susanne Johanna Väth (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
Recognising the increased demand for agricultural land, this comparative analysis examines the effect of large-scale land acquisitions on their surrounding institutional environment. An embedded case study design allows us to analyse two specific land deals in Ghana and Kenya. We find that insufficiencies in these countries' land governance systems are partly caused by discrepancies between de jure and de facto procedures; and that weak legal frameworks, coupled with poor enforcement, produce outcomes that depend to a large extent on the investors. We also find that large-scale land acquisitions have a feedback effect on the land governance system, which suggests that large-scale land acquisitions can be drivers of institutional change.
Keywords: 330